Ayurveda and infertility: Bridging traditional wisdom with modern challenges - Yadav, Poonam (International journal of health sciences, 2021)
If a clinical pregnancy cannot be achieved after 12 months or more of consistent, unprotected sexual activity, it is considered infertility. Vandhyatva has been used to describe infertility in Ayurvedic literature. Males and females may experience infertility for a variety of causes. For conception to occur and the pregnancy to be successfully completed, the four Ayurvedic factors Ritu, Kshetra, Ambu, and Beeja must be in their right states. A couple's ability to conceive may be impacted by factors like weight, nutrition, smoking, illnesses, substance misuse, environmental contaminants, medications, and family medical history. Either partner may have infertility. Men typically experience infertility due to limited or low-quality sperm, while women experience it when they are unable to produce eggs on a regular basis or when their fallopian tubes are damaged or obstructed, making it impossible for sperm to reach their eggs. Ayurvedic writings describe both the Shodhana and Shamana Chikitsa, which include Panchakarma, for Vandhyatva. This article discusses ayurveda concepts and management for female infertility, presenting Vandhyatva via an ayurveda lens.